The Effect of Curcuma longa (Tumeric) on Overall Performance of Broiler Chickens - AL-Sultan, S.I. (International Journal of Poultry Science, 2003)
The effect of Curcuma longa (tumeric) feed additive on overall performance of broiler chickens was investigated. The implication of different diet inclusion levels (0.25, 0.5 and 1.0%) of tumeric on body weight gain, feed conversion, carcass analysis, lymphoid organ weight index and blood cell count of broilers were tested comparing to untreated control birds. It had been found that the higher body weight gain (1344.5 g) was observed in birds fed diet contained tumeric at level of 0.5% followed by birds received o.25% (1329.8), 1% (1306) and control (1268.2). Moreover, the feed conversion of birds received 0.5% tumeric in their diets were the best (2.08) as compared to controls (2.47) and other treated groups (2.27 and 2.31). Regarding carcass analysis, the protein percent of breast and thigh muscles of birds in different treated and control groups were found nearly the same. The lower fat percentage (1.0%) were recorded in carcasses of birds received 1.0% tumeric followed by 0.5, control and 0.25%. On the other hand, the higher bursa and thymus weight indices were detected in birds received diet containing 0.5% tumeric, while the higher spleen weight index was observed in birds received feed contained 1.0% tumeric. The results of organo-leptic test revealed that tumeric did not induce any abnormal flavor, color or smell. The higher levels of tumeric inclusion (0.5 and 1.0%) increased both erythrocytic and total leukocytic count. It could be concluded that the use of tumeric as feed additive at level of 0.5% enhance overall performance of broiler chickens and cost effectiveness study should be conducted.